2018
DOI: 10.1101/246108
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

GtTR: Bayesian estimation of absolute tandem repeat copy number using sequence capture and high throughput sequencing

Abstract: BackgroundTandem repeats comprise significant proportion of the human genome including coding and regulatory regions. They are highly prone to repeat number variation and nucleotide mutation due to their repetitive and unstable nature, making them a major source of genomic variation between individuals. Despite recent advances in high throughput sequencing, analysis of tandem repeats in the context of complex diseases is still hindered by technical limitations.MethodsWe report a novel targeted sequencing appro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Genotype estimates from targeted long-read sequencing datasets were estimated using our tool VNTRTyper [12] with the improvements described in Methods. We also applied Tandem-genotypes [24] to determine the genotypes of TRs from long-read sequencing data.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Genotype estimates from targeted long-read sequencing datasets were estimated using our tool VNTRTyper [12] with the improvements described in Methods. We also applied Tandem-genotypes [24] to determine the genotypes of TRs from long-read sequencing data.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously demonstrated that targeted sequence capture of repetitive TR sequences are feasible using short-read sequencing technologies [12]. In this study, we demonstrate the targeted sequence capture of repetitive TRs using Oxford Nanopore long-read sequencing technologies.…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations